Enhancement of fiber-SPR sensor utilizing graphene oxide - M. Thirunavakkarasu, Punithavathi; Shabaneh, Arafat Abdallah Abdelwadod; Girei, Saad Hayatu; Yaacob, Mohd Hanif; Muhammad Noor, Ahmad Shukri (IEEE, 2013)
A graphene oxide layer deposited on top of a thin gold film of a fiber optic surface plasmon resonance sensor is investigated. Comparison is made on the sensing performance of modified sensor and a standard gold coated fiber optic surface plasmon resonance sensor. The graphene oxide coated sensor shows high sensitivity of approximately 400 nm/RIU to surrounding refractive index when tested with different liquids.